The Cleveland Clinic Manual of Headache Therapy - Tepper, Stewart J.; Tepper, Deborah E. (Springer New York : Imprint: Springer, 2011)
The Cleveland Clinic Manual of Headache Therapy is a hands-on, practical guide to diagnosis, work-up, and treatment of common headache disorders. Each chapter is written by a Cleveland Clinic Headache Center care provider. The book uses an evidence-based approach to sift through the wealth of available data and identify the most appropriate treatments. This manual is aimed at practicing neurologists and pain specialists, fellows and residents, and also primary care physicians. The Cleveland Clinic Manual is the most trusted source on this ever expanding and developing topic.